Pengaruh Pemberian Pupuk Kandang Ayam dan POC Ampas Tahu terhadap Pertumbuhan Tanaman Mentimun (Cucumis sativus L.) - Untung Subagyo; Pramono Hadi; Srie Juli Rachmawatie (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aimed to evaluate the effect of chicken manure and tofu waste–based liquid organic fertilizer (POC) on the growth and yield of cucumber (Cucumis sativus L.). The experiment was arranged in a factorial Completely Randomized Design (CRD) with two factors. The first factor was chicken manure applied at three doses: A1 (0.25 kg), A2 (0.5 kg), and A3 (0.75 kg per polybag). The second factor was tofu waste liquid organic fertilizer applied at three concentrations: T1 (100 ml), T2 (150 ml), and T3 (200 ml per polybag). The results showed that the application of 0.25 kg chicken manure significantly increased plant length, number of leaves, and root length. The application of tofu waste POC at 200 ml improved plant length, although its effect on other parameters was not consistent. A significant interaction between chicken manure and tofu waste POC was observed on plant growth and yield. The combination A1T2 produced the highest plant length (213.67 cm) and the best overall cucumber yield. These results indicate that the combined application of chicken manure and tofu waste POC is more effective than single fertilizer application.